Separation of triacylglycerols containing positional isomers of hexadecenoic acids by enantiomeric liquid chromatography-mass spectrometry - Řezanka, Tomáš; Lukavský, Jaromír; Rozmoš, Martin; Nedbalová, Linda; Jansa, Jan (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2022)
Triacylglycerols (TAGs) containing positional isomers of hypogeic (Hy), palmitoleic (Po), and palmitvaccenic (Pv) acids from three microorganisms (top-fermenting brewer's yeast Saccharomyces cerevisiae, green alga Coccomyxa elongata, and arbuscular mycorrhizal (AM) fungus Rhizophagus irregularis) were analyzed. Dozens of regioisomers and enantiomers of TAGs containing one, two or three hexadecenoic acids have been identified by means of reversed phase chromatography/mass spectrometry (RP-HPLC/MS). The regioisomers of TAGs containing two palmitic acids and any hexadecenoic acid were separated. Analysis of regioisomers of TAGs having one Pv residue showed that asymmetric molecular species such as PvPP or PPPv were dominant in Rhizophagus. TAGs were also analyzed on a chiral phase column and nine molecular species of TAGs containing two palmitic and any of three hexadecenoic acids were separated and identified. In the case of TAGs containing one palmitic and two hexadecenoic acids, the separation was successful only if the hexadecenoic acids were identical. Separation of TAGs containing three hexadecenoic acids was successful only if all three hexadecenoic acids were identical. Regardless of the type of TAG, it was found that TAGs in the AM fungus and containing palmitvaccenic acid bound at the sn-1 position of the glycerol backbone were dominant, suggesting similarity in the biosynthesis of the different TAGs. The covalent adduct chemical ionization method was used for identification of TAGs as adduct with (1-methyleneimino)-1-ethenyl ion, which reacted with double bond of the unsaturated fatty acid. Tandem MS thus makes it possible to identify TAGs containing various hexadecenoic acids.
Keywords: Hypogeic acids; Palmitic Acids; Enantiomeric liquid chromatography-mass spectrometry; hmotnostní spektrometrie; Cis-palmitvaccenic; triglyceridy; Mass Spectrometry; Chromatography, High Pressure Liquid; Chromatography, Liquid; Triglycerides; mastné kyseliny; vysokoúčinná kapalinová chromatografie; Palmitoleic; chromatografie kapalinová; Fatty Acids; kyseliny palmitové